Juridical Review of Online Fraud Under the Guise of Payment of Insurance Guarantee Funds in Indonesia - Ferina Krisdiyanti (UM Purwokerto Press, 2023)
The modes of operation of crime are increasingly diverse, one of which is online fraud. Particularly in economic activity around the world, transactions take advantage of the internet, which is popularly known as trading via the internet (e-commerce). In this article, the author discusses online fraud and the mode of payment of insurance funds in Indonesia. This fraud mode usually acts on behalf of JNE expedition services and takes advantage of the buyer's security in the JNE insurance calculation system. This study aims to explain the factors that lead to online fraud in Indonesia and to describe efforts to enforce and prevent online fraud with the insurance fund mode in Indonesia. The problems faced are: what are the factors that cause online fraud in Indonesia, and how are efforts to enforce and prevent online fraud by companies and the government in an integrated manner in Indonesia? Data were taken from secondary and primary sources in the form of online surveys and reports and studies from related institutions such as the police, the Indonesian Telecommunications Regulatory Body (BRTI), and the Association of Indonesian Internet Service Providers (APJII) with data collection and analysis methods. So based on this research, it is known that there are many factors that influence online fraud and follow-up that can be taken by the government according to applicable regulations so that it can have a good impact on the community to avoid cybercrime, especially online fraud.